2022
DOI: 10.4103/idoj.idoj_246_22
|View full text |Cite
|
Sign up to set email alerts
|

Role of oral minoxidil in patterned hair loss

Abstract: Recent studies have shown that low-dose oral minoxidil (OM) can be a safe and effective treatment of numerous hair disorders including male-patterned hair loss (MPHL) and female-patterned hair loss (FPHL). There are several practical advantages of OM over its topical formulation: enhanced cosmesis, cost-savings, and the possibility of co-therapy with other topical formulations or topicals used for camouflage. This treatment may be particularly helpful for patients who are unable to tolerate topical minoxidil o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…Furthermore, two other studies also confirmed the safety and efficacy of LDOM in young patients with alopecia [55, 56]. Nonetheless, further studies are required to establish the safety and efficacy of LDOM use in pediatric patients [47].…”
Section: Ldom Use In Pediatric Patientsmentioning
confidence: 92%
See 2 more Smart Citations
“…Furthermore, two other studies also confirmed the safety and efficacy of LDOM in young patients with alopecia [55, 56]. Nonetheless, further studies are required to establish the safety and efficacy of LDOM use in pediatric patients [47].…”
Section: Ldom Use In Pediatric Patientsmentioning
confidence: 92%
“…LDOM-associated side effects can be categorized into two groups: predictable, dose-dependent side effects (type A) and unpredictable, idiosyncratic reactions (type B) Table 3. Recommended dosage regimen, monitoring guidelines, contraindication, warnings, and management of side effects LDOM in treating male and female AGA [33,[47][48][49] Expert opinion-1 (AS) Expert opinion-2 (BMP) Expert opinion-3 (AT)…”
Section: Side Effects Of Ldommentioning
confidence: 99%
See 1 more Smart Citation
“…This can be attributed to various factors including undesired changes in hair texture, scalp irritation, unpleasant odor of the formulation, the development of allergies to minoxidil or its excipients, and the requirement to apply the medication twice daily. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a notable increase in the use of LDOM as a treatment choice for a diverse range of hair disorders, specifically targeting patterned hair loss (PHL). 5 This approach is gaining popularity due to its proven safety, efficacy, and favorable tolerability, making it a reliable therapeutic option. 1 , 6 This study aimed to evaluate the knowledge, attitudes, and practice patterns of dermatologists in Saudi Arabia regarding the utilization of LDOM for hair loss management.…”
Section: Introductionmentioning
confidence: 99%